LABORATORY EVALUATION OF SILTY SAND STABILIZED WITH CATIONIC ASPHALT EMULSION - Kurniadji
LABORATORY EVALUATION OF SILTY SAND STABILIZED WITH CATIONIC ASPHALT EMULSION,KURNIADJI 1998, PROGRAM MAGISTER SISTEM DAN TEKNIK JALAN RAYA, PROGRAM PASCASARJANA INSTITUT TEKNOLOGI BANDUNG. This thesis describes a laboratory investigation of soil stabilization using Cationic Asphalt Emulsion (CAE). Soil samples were taken from the Cilutung river at two locations, designated Cilutung I and Cilutung II. Both samples are classified as SM (USCS), A-2-4 (AASHTO) and differ mainly in the percentage finer than 75 micron (34.2% in the case of Cilutung I and 20.9% in the case of Cilutung II) CBR values determined for untreated Cilutung I and II soils were 13.47% and 15.34%,respectively. CBR tests made on the soils treated with 2%, 4%, 6%, 8% and 10% residual CAE indicated the maximum value to occur at a residual CAE content of 4%. After curing for 7 . days the CBR value of Cilutung I soil containing 4% residual CAE was 19.71%, that of Cilutung II soil 25.55%. With regard to the effect of curing period on CBR 'Value no consistent trend was observed. Relatively low CBR values were recorded for treated Cilutung I soil after curing periods of 14 and 21 days. Sample shrinkage may have accounted for this. Unconfined compressive strength (UCS) tests performed on treated samples of Cilutung I soil again showed the maximum value to occur at 4% residual CAE. UCS increased with increase in curing period; the UCS value of samples made with 4% residual CAE increased by 136% when curing period increased from 1 to 21 days. Coefficient of permeability reduces significantly with increase in residual CAE content; addition of 4% reduces the coefficient approximately by a factor of 10. On the basis of CBR values it appears that stabilization of the soils investigated using CAE does not result in a material suitable for use as a subbase, although stabilized Cilutung II soil is marginally acceptable. However the effect of curing on strength may not be accurately represented by the CBR test due to sample shrinkage and consequent reduction in the lateral confinement provided by the CBR mould